2014
DOI: 10.9734/jsrr/2014/4346
|View full text |Cite
|
Sign up to set email alerts
|

Climate Change and Growth Rate of Food Grain Output in Nigeria (1970-2010)

Abstract: The study examined climate change and growth rate of food grain output in Nigeria from 1970-2010. Time series data of maize, rice, millet, sorghum, wheat, temperature and rainfall were used for the study. Data analysis involved the use of Descriptive Statistics and the annual additive series (Trend) Analysis measured in years by getting the annual average of parameters which depict the factual position of climate change by variations of the weather parameters over time. Findings showed that the preferred weath… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…Food shortage is consequently linked with climate change. In contrast, it has been reported that temperature has no linkage with agricultural output (Igwe et al, 2014). Food shortages as a result of population increases are more obtained in Nigeria than climate change.…”
Section: Introductionmentioning
confidence: 94%
See 3 more Smart Citations
“…Food shortage is consequently linked with climate change. In contrast, it has been reported that temperature has no linkage with agricultural output (Igwe et al, 2014). Food shortages as a result of population increases are more obtained in Nigeria than climate change.…”
Section: Introductionmentioning
confidence: 94%
“…Climate change has brought with it changes in weather patterns that can have serious repercussions for all of us, upsetting seasonal cycles, harming ecosystems and water supply, affecting agricultural farming systems and food production, and also causing sea levels to rise (Igwe et al, 2014). Climate change is now a subject of worldwide concern.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations